2009
DOI: 10.3989/gya.108208
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fat on the fatty acid composition and cholesterol content of Hy-line and Warren hen eggs

Abstract: 350 throughout the study. The cholesterol egg content was higher at the animal fat plus soybean oil than at the animal fat or the olein plus soybean oil blend. Overall, results showed that changes in dietary lipids influenced fatty acid composition and hence atherogenic and thrombogenic indexes much more than the strain. KEY-WORDS: Atherogenic index -Cholesterol -Egg composition -Fatty acids -Hen-strain -Thrombogenic index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…The atherogenic and thrombogenic indexes in all the groups were optimal under a nutritional point of view (Table ) and were consistently lower that the results of González‐Muñoz et al . in layers fed different dietary fats.…”
Section: Resultssupporting
confidence: 55%
“…The atherogenic and thrombogenic indexes in all the groups were optimal under a nutritional point of view (Table ) and were consistently lower that the results of González‐Muñoz et al . in layers fed different dietary fats.…”
Section: Resultssupporting
confidence: 55%
“…On the other hand, the low cholesterol of B source was coincided with lower SFA content and lower HDL and LDL levels. Egg consumption is negatively affected by lipid, cholesterol, and fatty acid profiles, and recently, by atherogenic and thrombogenic indices and their health implications [ 5 , 8 , 10 ] due to higher cardiovascular threat associated with increasing levels of blood cholesterol [ 9 , 34 ]. However, the lipid and cholesterol contents of the present samples of eggs were found to be within the RDA for adult assuming daily consumption of one egg.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in fatty acids profiles and cholesterols contents of eggs have been found to be affected by lipid metabolism and fats/fatty acids composition in the laying hen diets [ 4 , 23 , 25 , 30 , 34 , 35 ]. However, there also are several other factors of second order that can affect lipid and cholesterol contents of eggs such as feed additives supplementation [ 6 , 7 , 24 ], age and strain of laying hens [ 28 , 30 ], dietary fiber [ 6 , 7 , 33 , 36 ], and flock husbandry [ 37 ] Cholesterol contents of eggs can also be manipulated by antioxidants supplementations [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies concluded that the fatty acid composition of eggs is dependent on the fatty acid composition of the feed of the laying hen [33,34,35,36,37,38,39]. Omega-3 fatty acids are one of the most sought after components in the functional food sector.…”
Section: Introductionmentioning
confidence: 99%